Pengaruh Penggunaan Agregat Kasar dan Metode Pemanasan Styrofoam Terhadap Beton Ringan - Ericko Aditya Chandra; Syafri Wardi; Angelalia Roza (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Concrete is a construction material that is widely used in various types of construction. One of the disadvantages of concrete is that its specific gravity is quite high, thus giving a big dead load on the structure. An alternative to overcome this weakness is using lightweight concrete. Therefore, in this study, lightweight concrete will be made with heated styrofoam. The styrofoam used is expanded polystyrene (EPS) type with a grain size of 4-5 mm. Heating of styrofoam the was done at 100°C for 15 minutes and 100°C for 25 minutes. The objective of this study is to evaluate the compressive strength and specific gravity of lightweight concrete using heated styrofoam material with different heating methods and the use of coarse aggregate in the lightweight concrete. Test sample in this study used heated styrofoam as 100% coarse aggregate replacement and 75% coarse aggregate replacement, while the remaining 25% uses coarse aggregate with a maximum grain size of 19.05 mm. To improve workability, a superplasticizer of 0.9% by weight of cement was used. The results of compressive test showed that the optimum value of compressive strength testing of 11.24 MPa in lightweight concrete with coarse aggregate and heated styroforom with the heating for 25 minutes at a temperature of 100°C. The concrete strength was classified into lightweight concrete lightweight structure. The specific gravity of the concrete is 1.578.38 kg/m3, which was classified into lightweight concrete based on SNI 03-3449-2002.